Central African Republic : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Requests for Waivers of Nonobservance of Performance Criteria and Augmentation of Access, and Financing Assurance Review; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Central African Republic. (IMF Staff Country Reports; Country Report ;, 2008)
This paper reviews the Central African Republic's three-year arrangement under the poverty reduction and growth facility. Concerns about the social impact of higher fuel prices have delayed implementation of an automatic pricing formula and caused serious fiscal losses. The new financing strategy is based on issuing debt instruments in the regional financial market to improve the domestic debt profile. IMF staff recommends completion of the second review, granting of waivers for nonobservance of performance criteria, and an augmentation of access.